Bioleaching of sphalerite mineralized with discrepant iron incorporations: experiment and DFT calculation - Yisheng Zhang; Xiaoyu Meng; Luyuan Zhang; Hong Zheng; Zhiwu Dong; Guohua Gu; Li Shen; Hongbo Zhao (Journal of Materials Research and Technology, 2022)
Iron incorporation is a natural phenomenon in the mineralization process of sphalerite (ZnS/Zn1-xFexS), which significantly affects the physicochemical properties of sphalerite and its metallurgical process. As an environmentally friendly technology, bioleaching has good compatibility for treating sphalerite feed from different sources, but the relationship between the different iron incorporations, bioleaching efficiencies and shifted physicochemical properties of sphalerite still needs clarification. To this end, three different sphalerite samples were investigated using experimental and simulation methods. The results of batch leaching and solid phase characterization confirmed the proportional relationship between Zn recoveries (3.38%, 33.59% and ∼100%) and iron incorporations (0.07%, 0.99% and 14.67%). Combining electrochemical testing and DFT calculations, a comprehensive mechanism containing solution conditions, surface reactivity and bulk physicochemical properties is proposed. As iron incorporation increases, the surface reactivity and bulk conductivity of sphalerite increase, but the strength of Zn–S bonds weakens, thereby promoting the efficiency of bioleaching. Variation in iron incorporation also changes the concentration of iron ions in the solution, which in turn regulates the biological activity and solution ORP and thus the bioleaching of sphalerite. The results obtained may provide a great reference for cleaner zinc extraction technology of sphalerite from different sources.